EFFECT OF VITEX TRIFOLIA ON ALLOXAN INDUCED DIABETIC RAT (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The leaves of plant Vitex trifolia by tradition used to treat of diabetes and correlated complications. Plants V. trifolia and Vitex negundo belongs to the Verbenaceae family, have some similar phytoconstituents. Leaf extract of Vitex negundo proven for its anti-diabetic property. Diterpenoids present in fruits of V. trifolia, they have anti-diabetic property. Vitexilactone a phytoconstituents in V. trifolia has insulin sensitizing property. The present study aimed to investigate in vivo anti-diabetic activity of aqueous leaf extract of V. trifolia in alloxanized diabetic albino wistar rats. Diabetes induced in rats by injecting alloxan hydrate at dose 150 mg/kg body weight. Diabetic rats were treated with 100 and 200 mg/kg of aqueous extract of V. trifolia for 21 days. Anti-diabetic activity of extract assessed by measuring blood glucose by Trinder's method, insulin by enzyme-linked immunosorbent assay, lipid profile by colorimetric methods, total proteins by Biuret method and calcium measured by using ligand Arsenazo III in an aqueous alkaline medium. Aqueous extract of V. trifolia did not show significant changes of blood sugar level in normal rats. But extract significantly reduces blood sugar, total serum cholesterol, triglycerides levels but increases insulin, HDL-cholesterol, total proteins, and calcium in diabetic rats. Aqueous extract of V. trifolia showed significant anti-diabetic activity in alloxan-induced diabetic rats.